2014
DOI: 10.1097/moo.0000000000000086
|View full text |Cite
|
Sign up to set email alerts
|

Noise-induced hearing loss

Abstract: Purpose of the review This article presents research findings from two invertebrate model systems with potential to advance both the understanding of noise-induced hearing loss mechanisms and the development of putative therapies to reduce human noise damage. Recent findings Work on sea anemone hair bundles, which resemble auditory hair cells, has revealed secretions that exhibit astonishing healing properties not only for damaged hair bundles, but also for vertebrate lateral line neuromasts. We present prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 57 publications
(131 reference statements)
0
16
0
Order By: Relevance
“…We found that the number of sound-elicited nerve potentials was mildly decreased and their peak response was strongly decreased in noise-exposed locust ears. In addition, the latency to first spike was significantly increased in noise-exposed locusts compared to controls which reflects increased latencies of CAPs measured in other noise-exposed auditory systems (Christie & Eberl, 2014;Sendowski et al, 2004;Pettigrew et al, 1984;;Van Heusden & Smoorenburg, 1981). Is it not known what changes take place in the auditory receptors to decrease spiking responses increase spike latency.…”
Section: In Vivo Electrophysiological Responses Of the Auditory Nervementioning
confidence: 96%
See 3 more Smart Citations
“…We found that the number of sound-elicited nerve potentials was mildly decreased and their peak response was strongly decreased in noise-exposed locust ears. In addition, the latency to first spike was significantly increased in noise-exposed locusts compared to controls which reflects increased latencies of CAPs measured in other noise-exposed auditory systems (Christie & Eberl, 2014;Sendowski et al, 2004;Pettigrew et al, 1984;;Van Heusden & Smoorenburg, 1981). Is it not known what changes take place in the auditory receptors to decrease spiking responses increase spike latency.…”
Section: In Vivo Electrophysiological Responses Of the Auditory Nervementioning
confidence: 96%
“…An increased sound amplitude elicited an increase in the nerve potentials (Figure 2Ci,ii,iii). Across hearing models hearing impairment is characterised by an increase in the latency of toneevoked electrical signals (Christie & Eberl, 2014;Coomber et al, 2014;Van Heusden & Smoorenburg, 1981;Salvi et al, 1980).…”
Section: In Vivo Electrophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Most work on the scolopidium has focused on development of the general structure and the ciliated nature of the dendrite (Caldwell & Eberl, 2002;Ebacher, et al, 2007;Jarman & Groves, 2013). More recent work on traumatized flies has developed flies as a model of hearing loss, validating the fruitfly as a meaningful model for hearing (Christie & Eberl, 2014;Christie et al, 2013). Only recently has work been done on the Johnston's Organ to understand the actual physiology of the structures and ion homeostasis (Roy et al, 2013).…”
Section: Ion Pumps In the Johnston's Organmentioning
confidence: 99%